Effectiveness Of Nursing Competency Of Service Quality In Installation Of Hospital Buleleng Hospital - Made Susiana (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Buleleng Regional General Hospital as a health service provider is concerned with the quality of its services. The quality of nurse services is the biggest part of the overall quality of hospital services because of the amount of contact with patients. The quality of service itself is influenced by the satisfaction and expectations and needs of patients being met. To meet the excellent quality of service, nurses need to have superior competence, namely basic knowledge, hard skills, soft skills, work ethics and legal aspects. The purpose of this study is to provide recommendations based on an analysis of the influence of nurse characteristics and competence on service quality. This research is a descriptive observational study, conducted from November. The study population was nurses working in the Inpatient Room, and the number of samples obtained was 80 nurses. The variables analyzed were individual characteristics, nurse competence, hard skills, soft skills, work ethics, and legal aspects. The results of this study indicate that age, length of work and position of head of the family at work have an influence on nurse competence. Length of work, and soft skills also have a positive influence on service quality. Conclusion: there is a significant effect between length of work, and nurses' soft skills on service quality. Variables that need to be improved and improved are registration letters, work licenses, training, and training to improve soft skills and work ethics